Kiwifruit branch compost reduces the bioavailability of the rare earth elements lanthanum and cerium in agricultural soils - Rui Cao; Buji Aer; Jiang Li; Yuyan Xie; Haitao Li; Hong Yang (Scientific Reports)
Abstract Rare earth elements are widely used due to their distinctive magnetic, optical and electrical properties. As a consequence, they inevitably enter the environment, potentially posing a threat to human health through the food chain. This experiment sought to investigate the impact of compost made by kiwifruit branches and sheep manure on the lanthanum (La) and cerium (Ce) in soils. The concentration of La and Ce in different state was detected, employing the Tessier’s method. The result indicated that, the proportions of La and Ce in the effective state, comprising exchangeable state, Bound to Carbonates state, and Bound to Iron and Manganese oxides state, were found to be markedly decreased; the conversion occurred predominantly between the 14th and 21st day after compost added. It was thus demonstrated that compost markedly accelerated the conversion of La and Ce from their effective state to a stable state; Furthermore, the effect was found to be proportionate to the quantity of compost added, with higher ratios yielding more pronounced outcomes. The effect is better with more compost for soil environment remediation, while a compost ratio of 10% can be selected for agricultural cultivation and cost control.